Implementation of Total Quality Management (TQM) and Six Sigma in the Learning Process in Vocational High Schools: Implementasi Total Quality Manajemen (TQM) dan Six Sigma dalam Proses Pembelajaran di Sekolah Menengah Kejuruan - Lasiana, Ninit; Hidayatulloh, Hidayatulloh (Indonesian Journal of Education Methods Development, 2022)
The purpose of this study is to describe the implementation of TQM and Six Sigma in the learning process at SMK Muhammadiyah 2 Taman Sidoarjo because the indicators of the failure of the learning process are the teachers have not mastered the learning material, have not been able to manage the class, have not mastered technology, and have not implemented learning strategies/methods. This research used a qualitative approach and data collection techniques using observation, interviews, and documentation. Sources of data for this research were principal, vice principal, quality assurance, teachers, students, and parents/guardians. The research data were analyzed and concluded. The results of the showed that: (1) The implementation of TQM in the learning process at SMK Muhammadiyah 2 Taman Sidoarjo was carried out according to the indicators of TQM success, including school services in meeting community needs and expectations, handling student complaints, and fulfilling infrastructure facilities to support teaching and learning activities ( KBM), increasing time discipline and work discipline, reducing complaints from the community by developing the best service culture and conducting evaluations; (2) The implementation of Six Sigma at SMK Muhammadiyah 2 Taman Sidoarjo was carried out using the DMAIC (Define, Measure, Analyze, Improve, Control) method, so that the learning process goes well, problems that occur gradually go down and do not reappear.